Maxim’s Flouting: An Analysis of Classroom Interaction - Abdi Wahyudi; Suhendra Yusuf; Zubaedah Wiji Lestari (Universitas Bengkulu, 2020)
This study focuses on analyzing the maxim flouting between the teacher and students of XI IPS in SMA PGRI 2 Bandung during classroom interaction. The objective of this study is to find out the types of flouting maxim produced by teachers and students. Furthermore, this study also investigates the effects of maxims flouting to classroom activity. This study implements descriptive qualitative as the method of the study. There are five instruments used in this study; those are observation checklist, field note, the script of recorded video, questionnaire, and interview. The result of the study shows that there were four types of maxims flouting produced by the teacher and students during classroom interaction. Moreover, the researchers found four adverse effects of flouting maxim in classroom activity.